Process Management of Enterprises on the Basis of Corporate Social Responsibility of Business (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The process management and corporate social responsibility of business, process of management on the basis of corporate social responsibility are considered. The structural model of the process management mechanism based on the corporate social responsibility of the enterprise is presented. The approaches to implementation of the developed mechanism are determined.In a new economy, the development of competition and globalization, the growth of duration and the reduction of the lag between global financial and economic crises affects the formation of new conceptual approaches to improving the process management of enterprises. One of these approaches is the application of the principle of corporate social responsibility of the business, which ensures the reconciliation of the internal and external interests of stakeholders, involving social investment, forming partnerships and building a social dialogue.It is noted that process management is understood as a set of principles, methods and tools that form the mechanism and are aimed at the formation and optimization of the business process system in order to increase the market value of not only the enterprise itself but also customers. When constructing an effective process management mechanism, it is necessary to take into account the principle of corporate social responsibility of the business.It is noted that the mechanism of process management on the basis of corporate social responsibility is a structure formed under the influence of the effect of economic laws, requirements of the regulatory legal system, is an open dynamic system and promotes the coherence of interests of the company and stakeholders, customers at the planning, organization, control corporate social responsibility of the enterprise.The structural model of the process management mechanism based on the corporate social responsibility of the enterprise provides identification and evaluation of problems in process management on the basis of corporate social responsibility, the implementation of forecasting their negative impact; definition of financial and economic resources that are aimed at increasing the market value of the enterprise; development of an effective system of management of activities based on the principle of social responsibility of business; development of measures to improve process management, evaluation and selection of the most effective ones;development of measures to improve process management, evaluation and selection of the most effective ones; implementation of their implementation through the system of current and strategic monitoring; evaluation of decisions made through continuous monitoring at all stages of implementation; providing feedback to stakeholders and customers; definition of directions of increasing the efficiencyof process management on the basis of corporate social responsibility.Due to the implementation of the corporate governance mechanism on the basis of corporate social responsibility, conditions are created for the advance development of business structures on the basis of timely identification and taking into account the signals of the internal and external environment of the operation of the enterprise.
Keywords: process management, enterprise, business, corporate social responsibility, forward development, mechanism